Chemistry of Triazene-Liquid Crystals: A Review - M. Abdulhameed, Zahraa; Jber, Nasreen Raheem (Al-Nahrain Journal of Science, 2025)
This review focuses on star-shaped liquid crystals that possess a highly organized and elongated molecular design, which enables them to exhibit favorable ferroelectric and ionic conductivity functions due to the electron delocalization resulting from π-π stacking conjugation and the electrostatic attraction of ions. The motivation for creating an ionic liquid crystal with a nematic phase is due to its potential engineering uses. The nematic phase is recognized for having the highest fluidity among all liquid crystalline phases. This makes it possible to position the nematic phase by applying an external electric or magnetic field widely utilized in electro-optical electronics. The chemistry of liquid crystals, specifically the state chemistry of matter, involves compounds of chemicals containing features of liquid crystals. Biological sensors made from liquid crystal materials enable monitoring biological phenomena without labels. Liquid crystalline polymers are employed to replicate color-generating structures. Liquid crystal compounds are commonly known as a distinct state; however, their impact on contemporary procedures has been significant. Derived from cholesterol, liquid crystals are molecules often studied and handled by biologists and biomedical engineers.